Consistency of drug-resistant mutations in plasma and peripheral blood mononuclear cells of patients with treatment-naïve and treatment-experienced HIV-1 infection - Ma, Jie; Chen, Zhaoyun; Fu, Chaohong; Wei, Shuguang; Liu, Jinjin; Yang, Xuan; Chen, Xuhui; Zhao, Qingxia; Sun, Yan; Huo, Yuqi (Frontiers in Cellular and Infection Microbiology, 2023)
Organization for all patients infected with human immunodeficiency virus type 1 (HIV-1) undergoing care or switching regimes due to failure with previous antiretroviral therapy (ART). Patients with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) who meet the criteria for free testing for genotypic drug resistance due to poor adherence in Henan Province may resume their previous regimens before resampling. Therefore, resistance testing based on plasma RNA can fail in a proportion of patients. Resistance testing based on peripheral blood mononuclear cells (PBMCs) is an alternative option. In this study, we investigated the differences in drug-resistant mutations (DRMs) between plasma HIV RNA and proviral DNA in treatment-experienced and treatment-naïve patients. Matched plasma RNA and proviral DNA samples of 66 HIV-1 infected treatment-naïve and 78 treatment-experienced patients were selected for DRM analysis and comparison.DRMs were detected in 27.3% (18/66) of treatment-naïve and 80.8% (63/78) of treatment-experienced samples. Resistance to at least one drug was detected based on analysis of plasma RNA and proviral DNA in 7.6% (5/66) and 9.1% (6/66) of treatment-naïve patients and in 79.5% (62/78) and 78.2% (61/78) of treatmentexperienced patients, respectively. Furthermore, 61/66 (92.4%) of treatment-naïve patients showed concordant RNA and DNA drug resistance. When drug resistance was defined as intermediate and high, the concordance of drug resistance profiles of paired RNA and proviral DNA samples derived from treatment-naïve patients were up to 97.0% compared with only 80.8% (63/78) in treatment-experienced patients.Our data indicate that drug resistance testing based on plasma RNA or proviral DNA might be interchangeable in treatment-naïve patients, whereas plasma RNA-based testing remains the best choice for drug resistance analysis in patients with ART failure in clinical practice.